2022
DOI: 10.3390/medicina58030437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Non-Invasive Radiofrequency Diathermy in Pelvic Floor Disorders: A Systematic Review

Abstract: Background and Objectives: In recent years, the use of radiofrequency diathermy in pelvic floor disorders has grown proportionally to the interest in this specialty. Despite the common use of this therapy among pelvic floor physiotherapists, little is known about its effects and effectiveness in pelvic floor disorders. For this reason, the aim of the present review is to assess the effects of non-invasive 300 kHz–1 MHz radiofrequency diathermy in the treatment of pelvic floor disorders. Materials and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…To date, positive effects of TECAR therapy on pain relief after sports injuries or in Peyronie’s disease have been observed [ 17 , 18 ]. So far, one review has been published on the use of TECAR in pelvic structural dysfunction [ 30 ]. The review identified two studies on pain assessment as promising; Fernández-Cuadros et al were successful with participants with chronic pelvic pain and dyspareunia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, positive effects of TECAR therapy on pain relief after sports injuries or in Peyronie’s disease have been observed [ 17 , 18 ]. So far, one review has been published on the use of TECAR in pelvic structural dysfunction [ 30 ]. The review identified two studies on pain assessment as promising; Fernández-Cuadros et al were successful with participants with chronic pelvic pain and dyspareunia.…”
Section: Discussionmentioning
confidence: 99%
“…Five participants were treated for three menstrual cycles, with improvements in the intensity of painful menstruation, sexual pain, and myofascial pain. These results cannot be considered generalizable due to the small sample size and the lack of a control group, and encourage the design of a larger study [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its effects on socio-psychological problems and have a significant effect on the economy. Regarding the effect of TECAR therapy in improving the strength and activity of the muscles ( González-Gutiérrez et al, 2022 ). The goal of our research is to see how effective TECAR is in treating mild and moderate cases of females with SUI.…”
Section: Introductionmentioning
confidence: 99%